Advances in percutaneous stone surgery - Christopher Hartman; Nikhil Gupta; David Leavitt; David Hoenig; Zeph Okeke; Arthur Smith (Asian Journal of Urology)
Treatment of large renal stones has changed considerably in recent years. The increasing prevalence of nephrolithiasis has mandated that urologists perform more surgeries for large renal calculi than before, and this has been met with improvements in percutaneous stone surgery. In this review paper, we examine recent developments in percutaneous stone surgery, including advances in diagnosis and preoperative planning, renal access, patient position, tract dilation, nephroscopes, lithotripsy, exit strategies, and post-operative antibiotic prophylaxis.